PENGARUH MINAT BELAJAR TERHADAP KEAKTIFAN BELAJAR MATEMATIKA MELALUI APLIKASI GOOGLE CLASSROOM - Aji Sugiarto (Prodi Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Muhammadiyah Parepare, 2024)
This research aims to determine the influence of interest in learning on activeness in learning mathematics through the Google Classroom application in class The instrument used in this research was a questionnaire consisting of a learning interest questionnaire and a mathematics learning activity questionnaire. The results of the research that has been carried out show that interest in learning has a positive effect on activeness in learning mathematics through the Google Classroom application for class X UPT students at SMA Negeri 1 Parepare. This is shown by 1) the interest in studying mathematics of class Classroom students in class which means that interest in learning influences active learning in mathematics by 56.5%.